State‐of‐the‐art and some considerations on thermal load analysis and thermal management for hydraulic system in MEA. Issue 13 (12th April 2018) - Li, Dong; Dong, Sujun; Wang, Jun; Li, Yunhua
Abstract : Hydraulic system is an important part in aircraft secondary energy‐resource system, its pumping source contains engine‐driven pump (EDP) and electrical‐motor‐driven pump, and it is in charge of safe and reliable power transmission for flight control actuation in the aircraft. The power losses in hydraulic system will inevitably result in the temperature rise of hydraulic system, and which will seriously affect the performances of hydraulic system. Therefore, to cool thermal load and control hydraulic oil temperature in allowable range is necessary. This survey paper reviews the present status of thermal load analysis and thermal management of the aircraft hydraulic system, especially more electric aircraft (MEA), and proposes fuel/hydraulic oil heat exchanger is the more effective heat dissipation component for fuel oil as heat sink be directly burned in burner without the extra cooling cost. Moreover, this paper provides some considerations and thorough analysis on thermal management schemes and actuators in power by wire transmission system of MEA. The main summarised conclusions and proposed considerations have the important practical significances to design and high efficient operation of airborne hydraulic system.